Effectiveness of the Strengthening Families Programme 10–14 in Poland for the prevention of alcohol and drug misuse: protocol for a randomized controlled trial - Okulicz-Kozaryn, Katarzyna (BioMed Central, 2012)
BACKGROUND: Alcohol and other drug use and misuse is a significant problem amongst Polish youth. The SFP10-14 is a family-based prevention intervention that has positive results in US trials, but questions remain about the generalizability of these results to other countries and settings. METHODS/DESIGN: A cluster randomized controlled trial in community settings across Poland. Communities will be randomized to a SFP10-14 trial arm or to a control arm. Recruitment and consent of families, and delivery of the SFP10-14, will be undertaken by community workers. The primary outcomes are alcohol and other drug use and misuse. Secondary (or intermediate) outcomes include parenting practices, parent–child relations, and child problem behaviour. Interview-based questionnaires will be administered at baseline, 12 and 24 months. DISCUSSION: The trial will provide information about the effectiveness of the SFP10-14 in Poland. TRIAL REGISTRATION: International Standard Randomised Controlled Trial Number: ISRCTN89673828